“Diversidade e Evolução de Vertebrados” na formação de professores: percepções, desafios, dificuldades e possibilidades de superação - Antunes, Taine Vandressa (Universidade Federal de São Carlos, 2016)
Vertebrates constitute the subphylum known as Vertebrata of the Phylum Chordata whose present diversity is fascinating. Although these animals attract attention because they are common in our daily lives, the largest challenge is the understanding of the biological diversity gathered under the same evolutionary history that should overcome the plethora of names and become significant in the teaching-learning process.It is fundamental, therefore, to understand how university students learn and the difficulties faced in the construction of knowledge, being crucial the constant search for strategies, didactic tools and alternatives to facilitate that construction. Thus the aims of the present study involved the qualitative survey of perceptions of undergraduate students of the licentiate degree in Biological Sciences at UFSCar - Campus Sorocaba regarding the learning of the contents of the discipline Diversity and Evolution of Vertebrates, discussing the main difficulties and contributions of this discipline to the Teacher training. The results showed that students difficulties involved basal groups mainly before Tetrapoda, concepts in Phylogenetic Systematics, "Reptilia" and the evolution of the temporal fenestra. Moreover, the lack of proper material such as illustrated guides to support examination of specimens in Lab Classes was cited by many students as an important limitation to learning. Seeking a proposal to cope with the difficulties was elaborated resulting in the Practical Guide: Diversity and Evolution of Vertebrates, a digital material to support Lab Classes, and it was suggested the development of an app related to the guide aiming at facilitating the access to updated contents and to optimize the teaching-learning process.
"Diversity and Evolution of Vertebrates" in the generation of teachers: perceptions, challenges, difficulties and possibilities to overcome
Keywords: Ensino de Zoologia de vertebrados; Ensino Universitário; Processo de ensino-aprendizagem; Proposta didática; Teaching of Vertebrate Zoology; University Teaching; Teaching-learning process; didactic proposal; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS HUMANAS::EDUCACAO